Intention to shift from short-acting to long-acting methods of contraceptives and its associated factors in Gondar city, northwest Ethiopia: Using the theory of planned behavior - Fekadu, Edom Retta; Azale, Telake; Berhe, Resom; Nigusie, Adane; Azene, Zelalem Nigussie; Wolde, Maereg (Frontiers in Reproductive Health, 2022)
Background: Despite its effectiveness, the intention and utilization of long-acting contraceptive methods are very low in many developing countries and the use of long-acting contraceptive methods has not kept pace with that of short-acting methods such as oral contraceptives and injectables. Therefore, this study aimed to assess the intention of using long-acting contraceptive methods and associated factors among women currently using short-acting contraceptive methods. Methods: Institution-based cross-sectional study was conducted from March 19 to April 19, 2017. The study included 515 short-acting contraceptive users found in Gondar city that were selected from the study population using a systematic random sampling technique. A structured pre-tested questionnaire based on the theory of planned behavior was used to collect data. Both descriptive and analytical statistical procedures were used. Simple and multiple linear regression analyses were carried out. SPSS version 20 was used for the analysis of data. Multiple linear regression was carried out to see the association between intention and sociodemographic variables, past contraception experience, attitude, subjective norm, and perceived behavioral control, and with 95% confidence interval and a p-value of less than 0.05 was used to detect statistical significance. Results: The magnitude of intention to use long-acting contraceptive methods was 39.8%. Intention to use long-acting contraceptive methods was higher for women whose husbands were farmers when compared to women whose husbands were government employees (β =0.49, 95% CI: 0.41, 0.72). Number of children wanted (β = - 0.19, 95%CI: -0.28, -0.1), attitude (β= 0.34, CI: 0.23, 0.46), subjective norm (β=19, 95%CI: 0.12, 0.27) and perceived behavioral control (β=0.18, 95%CI: 0.06, 0.3) were factors significantly associated with intention to use long-acting contraceptive methods. Conclusions: Intention to use long-acting contraceptive methods was low. Interventions that focus on women’s attitudes toward long-acting contraceptive methods and support groups, peer education, social mobilization, and persuasive communication could promote the intention to use long-acting contraceptive methods.